Can non-physician health-care workers assess and manage cardiovascular risk in primary care? - Dele O Abegunde; Bakuti Shengelia; Anne Luyten; Alexandra Cameron; Francesca Celletti; Sania Nishtar; Vasu Pandurangi; Shanthi Mendis
OBJECTIVE: To ascertain the reliability of applying the WHO Cardiovascular Risk Management Package by non-physician health-care workers (NPHWs) in typical primary health-care settings. METHODS: Based on an a priori 80% agreement level between the NPHWs and the "expert" physicians (gold standard), 649 paired (matched) applications of the protocol were obtained for analysis using Kappa statistic and multivariate logit regression. FINDINGS: Results indicate over 80% agreement between raters, from moderate to perfect levels of agreement in almost all of the sections in the package. The odds of obtaining a difference between raters and a benchmark are not statistically significant. CONCLUSION: Applying the WHO Cardiovascular Risk Management Package, NPHWs can be retrained to reliably and effectively assess and manage cardiovascular risks in primary health-care settings where there are no attending physicians. The package could be a useful tool for scaling up the management of cardiovascular diseases in primary health care.